A nők tanulmányozása a földrajzban, avagy: van-e létjogosultsága a feminista geográfiának Magyarországon. - Timár, Judit (Tér és Társadalom, 1993)
The geography of gender, and its different versions, like geography of women and feminist geography, have become into the frontline of the profession in many countries of the world recently. The publications in feminist geography, coming out in increasing numbers since the end of the 1960s, highlighted the different aspects of the relationship between men and women, their different social role and the transformation of the cultural landscape. Similar to other East-Central European countries, this type of researches has not been carried out by geographers in Hungary until now. However, those sociologists and economists, who recognized the role of the relationship between men and women in transforming the society did not investigate the space-transforming effects of this relationship. For this reason, this short study tries to answer the following questions: –Why is Hungarian geography uninterested in investigating the relationship between the specific role of the two sexes and the spatial forms and processes; –Which could be the most important research fields of feminist geography (geography of gender, geography of women); –Can these researches result in practical findings and conclusions? 1.) We should ask the question whether the lack or the considerable delay of feminist geography could be explained with the development/structure of geography as it is, or with the social environment itself – or probably with both of them. At the end of the 1960s, when feminist geography appeared in the West, Hungary followed the Soviet example in this field as well, consequently there was no human geography, but economic geography instead in Hungary then. The researches concentrated on production and on the macro tendencies, and the investigation of spatial relations limited itself to the delineation of regions. Geography, which observed human beings one-sidedly, was rather neutral to gender than biassed. From the 1970s, the spatial tendencies that gradually became small scaled, drew the attention on the problems of the settlements, and also on the problems of rural people. Social functions were given much wider interpretation, but the stress continued to be on central decisions and on the answers given to them, primarily at settlement level. The specific strategies of the different social strata and groups, and their role in spatial formations were seldom worded, and even if yes, in the form of a simple registration of the differences. It seems to us, that the attitudes, standpoint and aspects applied by geography facilitated the science to realize the significance of feminist geography only through the spread of the social-geographical school. The social environment itself created different conditions, and caused different problems than in the market economies. According to the Marxist ideology prevailing in the socialist countries, the expropriation of women is automatically terminated with the end of the class society. Consequently, the equality of sexes was declared. For example, the right of women to work was declared, and the numerous disadvantageous situations of women were concealed with the "masculinization" of women. As one of the most important objectives of the Western feminist movements was to gain equal chances in terms of employment, the paternalist socialist state declared the women's movement "irrational", and suppressed them, similarly to other civil organizations. Tensions between other social groups, and the rural and urban living conditions seemed to be more striking, thus these attracted the attention of the researchers. At the same time, due to the full employment of women, and delayed urbanization, the urban space was not divided lnto "masculine city" and "feminin suburbs" in this region. The spatial isolation of women, aimilar to that of the American women, thus took place only with the introduction of maternity leave and childcare allowance, and especially in the new housing estates, being far from the city centre and planned inhumanly. However, these problems rather became socialpsychological and urban issues, and urban geography was cut off from them. The transformation into a market economy and the democratization of political life created a new situation which resulted in new conditions for the relationship between men and women. The existence of any kind of social inequality is given a political echo, and the wide variety of ideologies and values is clearly expressed. The women's organizations which are slowly Organized within the parties but also outside the parties call the attention not only to the old, hut also to the newly appearing problems and tensions, and fact-finding researches are needed. 2.a.) The transforming relationship between space and society, and within this, of men and women rise several questions which can only be answered with the help of geographical approach. One of the most important fields of geography of women could be the investigation of the spatial inequalities in the social conditions of men and women. Female employment is one of the most frequently used indicator of emancipation, and this clearly indicates the regional differences as well. Women are employed in jobs with lower salaries and requiring lower qualifications than men. As opposed to men who usually work as skilled workers„ the majority of women earn their living as administrative and unskilled workers. In the villages, the majority of women belong to this category: in the outskirts, they – together with the semi-skilled workers – give two-thirds of all the active women earner. Though the gradual improvement of the educational levei resulted in the equalization between the two sexes, women still have to face considerable disadvantages. The differences in public education in terms of space and settlements call our attention to the fact that in the investigation of the chances for further education the investigation by sexes should be connected with the analysis by social origin and by settlement type. Undoubtedly, those researches would provide us with the most interesting results which can exceed the limits of statistical data supply existent in this field. A questionnaire studying the suburbs of Kecskemét examplifies that one can provide a more detailed picture about the relationship between men and women in the family, if knowing the differences in the educational level, earnings, and commuting habits of the married couple or those living together. Finally, the feminist geographers should not forget in the course of revealing the inequalities between the two sexes that in terms of chances we cannot limit ourselves to studying the relationship between men and women, and even less to husbands and wives. Completely different, but equally important issues can be raised by studying the relationship between the mother and the son, the father and the daughter, the brothers and the sisters, etc. The unequal regional development of childcare institutions, for example, creates great differences among women. Between 1985 and 1991, 457 nurseries closed down, depriving this way several villages from these institutions and putting the women living in these villages into far more difficult situation than their counterparts in the cities. On the other hand, however, the danger of impoverishment has increased, and the chances to live at a relatively high standard decreased among the young urban couples with children. 2.b.) The other, large research area of geography of women could be studying the differences between men and women in terms of space, producing and using space. According to the findings of the investigations carried out near Kecskemét, in an average, 68-83 % of the married couples not only do not work in the same place, but do not even work in one economic sector. Consequently, the differences between their use of space and daily spatial path – in contrast to the Western countries – is rather influenced by the differences in their place in production, and not so much by the separation of housework and work for money. Investigating the differences in the comprehension of space and the need for space between men and women could be the tank of small-scale geography, which is not very popular in Hungary yet. Sexual characteristics are often quoted in the argumentations mentioned to support the ideology that "women should stay at home", whereas they are always forgotten when planning and designing the flats made of prefabricated elements and the new housing estates. This is also a clear proof of the applicability of feminist-geographical research findings. 3.) It would be especially useful, if construction activities, regional planning, regional development and local policy could be influenced with correct research results. The situation of women could be improved considerably if their "externally" formed "Lebensraum" would meet their lifestyle better. At this point, however, we cannot avoid the question, whether the interests of women are better served by regional policy and regional development that meet the actual gender division of labour, conserving that structure this way, or by emancipation realized in all aspects of life.